2015
DOI: 10.1039/c4nj01556h
|View full text |Cite
|
Sign up to set email alerts
|

Predicting self-assembly and structure in diluted aqueous solutions of modified mono- and bis-β-cyclodextrins that contain naphthoxy chromophore groups

Abstract: The water diluted solution behaviour of mono-and bis-b-cyclodextrin (mono-and bis-CD) derivatives, whose appended groups and inter-CD linkers contain a naphthoxy chromophore moiety, has been studied using steady-state and time-resolved fluorescence techniques, circular dichroism and molecular modelling.Mono-CD derivatives form non-covalent dimeric tail-to-tail supramolecular structures via the mutual partial penetration, through their primary sides, of axially oriented naphthoxy appended groups and the selfinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…This bisignal can be attributed to an exciton coupling (EC), which occurs when two chromophores are close in the space and at least one of them exhibits relatively large molar absorptivity . It must arise from the intermolecular interaction between two azobenzene modules, supporting the formation of a face-to-face 3 - E -isomer dimeric species …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This bisignal can be attributed to an exciton coupling (EC), which occurs when two chromophores are close in the space and at least one of them exhibits relatively large molar absorptivity . It must arise from the intermolecular interaction between two azobenzene modules, supporting the formation of a face-to-face 3 - E -isomer dimeric species …”
Section: Resultsmentioning
confidence: 99%
“… 33 It must arise from the intermolecular interaction between two azobenzene modules, supporting the formation of a face-to-face 3 - E -isomer dimeric species. 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the preparation of a large number of CD-derivatives by MW-assisted CuAAC regioselective cycloadditions has been described. A selected series of derivatives are depicted in Scheme 10 : CD-acryloyl derivative [ 60 61 ], β-CD/dye derivatives [ 31 , 62 64 ], CD-ionic liquid hybrids [ 65 66 ], CD-based iminosugar conjugates [ 67 ], water-soluble CD homo- and heterodimers [ 68 69 ], trimers [ 70 71 ] and oligomers [ 72 ] of α-, β- and γ-CD have all been successfully produced. This wide variety of compounds was obtained in good to excellent yield under MW irradiation (from 20 min to 3 h at 75 °C to 100 °C).…”
Section: Reviewmentioning
confidence: 99%
“…Most reported examples of CD-aromatic conjugates focus on single position-linked derivatives that keep considerable mobility, which limits accurate three-dimensional definition, however (Gamieldien et al, 2010). Covalently bridging CD building blocks with aromatic tethers has been advantageously exploited for preorganization purposes in some cases (Carmona et al, 2015; Sun et al, 2015; Gallego-Yerga et al, 2018). Alternatively, prototypes featuring a two-point connected aromatic component at either the primary (Yang et al, 2008; Le Gac et al, 2016; Ménand et al, 2016, 2018; Yan et al, 2017) or the secondary rim (Balbuena et al, 2007, 2013) in a monomeric CD derivative have been reported, allowing unprecedented control over the topological and supramolecular attributes.…”
Section: Introductionmentioning
confidence: 99%